Primary thyroid gland myxofibrosarcoma: a case report and review of the literature - Maria Chara Stylianidi; Lena Haeberle; Matthias Schott; Yuriko Mori; Christina Antke; Frederick Lars Giesel; Gerald Antoch; Irene Esposito; Wolfram Trudo Knoefel; Andreas Krieg (Surgical Case Reports, 2022)
Abstract Background Myxofibrosarcoma is a common soft tissue sarcoma of the extremities, which occurs very rarely in the thyroid gland. Case presentation We report the case of a 61-year-old male who presented with a swelling of the left side of the neck and a newly emerged hoarseness. Ultrasound depicted a hypoechoic thyroid nodule with microcalcifications that was highly suspicious for malignancy. He underwent a left hemithyroidectomy. Histopathological examination and immunohistochemical studies revealed a myxofibrosarcoma of the thyroid gland. Conclusion Myxofibrosarcoma of the thyroid gland is extremely rare. The diagnosis is based on histopathological features. Radical surgery achieving tumor-free resection margins remains the only chance for cure. However, the role of radiotherapy and/or chemotherapy is still under debate. Due to their high tendency for locoregional recurrence, a close follow-up after surgery is mandatory.